Acromioclavicular joint dislocation: a Dog Bone button fixation alone versus Dog Bone button fixation augmented with acromioclavicular repair—a finite element analysis study - Sermsak Sumanont (2018)
© 2018, Springer-Verlag France SAS, part of Springer Nature. Background: Suspension suture button fixation was frequently used to treat acromioclavicular joint (ACJ) dislocation. However, there were many studies reporting about complications and residual horizontal instability after fixation. Our study compared the stability of ACJ after fixation between coracoclavicular (CC) fixation alone and CC fixation combined with ACJ repair by using finite element analysis (FEA). Materials and methods: A finite element model was created by using CT images from the normal shoulder. The model 1 was CC fixation with suture button alone, and the model 2 was CC fixation with suture button combined with ACJ repair. Three different forces (50, 100, 200 N) applied to the model in three planes; inferior, anterior and posterior direction load to the acromion. The von Mises stress of the implants and deformation at ACJs was recorded. Results: The ACJ repair in the model 2 could reduce the peak stress on the implant after applying the loading forces to the acromion which the ACJ repair could reduce the peak stress of the FiberWire at suture button about 90% when compared to model 1. And, the ACJ repair could reduce the deformation of the ACJ after applying the loading forces to the acromion in both vertical and horizontal planes. Conclusion: This FEA supports that the high-grade injuries of the ACJ should be treated with CC fixation combined with ACJ repair because this technique provides excellent stability in both vertical and horizontal planes and reduces stress to the suture button.